Sentinel lymph node biopsy for early oral cancers: Westmead Hospital experience. Issue 1 (23rd November 2016) - Abdul‐Razak, Muzib; Chung, Hsiang; Wong, Eva; Palme, Carsten; Veness, Michael; Farlow, David; Coleman, Hedley; Morgan, Gary
Abstract : Background: Sentinel lymph node biopsy (SLNB) has become an alternative option to elective neck dissection (END) for early oral cavity squamous cell carcinoma (OCSCC) outside of Australia. We sought to assess the technical feasibility of SLNB and validate its accuracy against that of END in an Australian setting. Methods: We performed a prospective cohort study consisting of 30 consecutive patients with cT1 ‐ 2 N0 OCSCC referred to the Head and Neck Cancer Service, Westmead Hospital, Sydney, between 2011 and 2014. All patients underwent SLNB followed by immediate selective neck dissection (levels I–III). Results: A total of 30 patients were diagnosed with an early clinically node‐negative OCSCC (seven cT1 and 23 cT2), with the majority located on the oral tongue. A median of three (range: 1–14) sentinel nodes were identified on lymphoscintigraphy, and all sentinel nodes were successfully retrieved, with 50% having a pathologically positive sentinel node. No false‐negative sentinel nodes were identified using selective neck dissection as the gold standard. The negative predictive value (NPV) of SLNB was 100%, with 40% having a sentinel node identified outside the field of planned neck dissection on lymphoscintigraphy. Of these, one patient had a positive sentinel node outside of the ipsilateral supraomohyoid neck dissection template. Conclusion: SLNB for early OCSCC is technically feasible in an Australian setting. It has a high NPV and can potentially identify at‐risk lymphatic basins outside the traditional selective neck dissection levels even in well‐lateralized lesions.